Effectivity of BS4 enzyme complex on the performance of laying hens fed with different ingredients - Arnold P. Sinurat; Tresnawati Purwadaria; Tuti Haryati (Indonesian Center for Animal Research and Development (ICARD), 2016)
An experiment was carried out to evaluate the effectivity of an enzyme complex produced by Eupenicilium javanicum BS4 on the performance of laying hens fed with different feed ingredients. Three diets were formulated with similar nutrients (protein, ME, digestible amino acids, Ca and available P) value to meet the nutrient requirement of laying hens. Diets were formulated based on maize, palm kernel cake (PKC) or rice bran. The diets were either supplemented or not with BS4 enzyme complex and fed to Isa Brown pullet from 19 to 37 weeks old. Each diet was fed to 24 birds and the performances were recorded. Data were analysed statistically with 2 X 3 factorial design with six replicates. Results showed that supplementation of BS4 enzyme into laying hens diet did not influence body weight change, feed intake, mortalities, egg weight and egg shell thickness but significantly increased egg production (P<0.05) and the FCR (P<0.01) in any feedstuff tested. It also improved egg yolk colour score on diet contained 20% PKC. Laying hens fed 20% PKC produced more eggs than those fed maize or rice bran. The egg shell of laying hens fed rice bran were thicker than those fed with maize or PKC. It is concluded that BS4 enzyme complex is effective when supplemented into laying hens diet.